2011
DOI: 10.1590/s1516-18462011005000018
|View full text |Cite
|
Sign up to set email alerts
|

Lesões organofuncionais do tipo nódulos, pólipos e edema de Reinke

Abstract: TEMA: lesões organofuncionais são formações benignas decorrentes de comportamento vocal alterado e inadequado, sendo as mais comuns: nódulos, pólipos vocais e edema de Reinke. OBJETIVO: realizar um estudo comparativo dos dados descritos na literatura sobre prega vocal normal e afecções organofuncionais do tipo nódulos, pólipos e edema de Reinke. O estudo foi realizado por meio de um levantamento bibliográfico em periódicos indexados no Science Direct, periódicos Capes, LILACS, SciELO, MedLine e Scopus e livros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
(162 reference statements)
1
8
0
9
Order By: Relevance
“…The data presented show that smokers have on average a moderate change in vocal parameters, and nonsmokers do not have significant change, confirming the literature data. 9 Smoking is a major risk factor for changes in the conformation of the vocal folds, producing mainly glottic edema. This edema decreases the fundamental frequency of the voice, making it more severe, with hoarse breaks, leaving it unstable and odd-sounding to listeners, who interpret this change as hoarseness.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented show that smokers have on average a moderate change in vocal parameters, and nonsmokers do not have significant change, confirming the literature data. 9 Smoking is a major risk factor for changes in the conformation of the vocal folds, producing mainly glottic edema. This edema decreases the fundamental frequency of the voice, making it more severe, with hoarse breaks, leaving it unstable and odd-sounding to listeners, who interpret this change as hoarseness.…”
Section: Discussionmentioning
confidence: 99%
“…Although polyp being one of the most frequent benign lesions in vocal folds 4 , the case series studies or clinical trials showed a limited number of participants, which varied from three to twenty 27, 28,30,31 . Despite the phonotraumatic etiology in the vocal nodule, whose initial therapeutic indication is speech therapy, referring patients with vocal polyp to speech therapy before surgical procedure is a restricted practice of some otorhinolaryngologists 12 , which hinders the recruitment of participants for the development of prospective researches.…”
Section: Methodsmentioning
confidence: 99%
“…Vocal fold polyps are lesions of benign mass, generally unilateral, which can be classified into sessile or pendunculated in relation to form, or into gelatinous (translucent), fibrous (organized) and angiomatous (hemorrhagic) [2][3][4][5][6][7][8] in relation to histological characteristics 9 . However, other irritation…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco modifies the layers of the vocal fold, which changes the vocal fold's vibratory cycles and vocal quality (7) . The perceived vocal characteristics of individuals with Reinke's edema are: roughness, low pitch, fluid voice, creaky voice and monoloudness (2,8,9) . The acoustic data usually presents: lower fundamental frequency (F 0 ), changes in jitter, shimmer, harmonic-to-noise ratio and reduction in the maximum phonation time (10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…Women with Reinke's edema commonly complain about being addressed as men, especially in phone calls. However, there are only a few studies regarding this condition (9,14) . Recently, a study showed that women with Reinke's edema self-assess their voices as masculine.…”
Section: Introductionmentioning
confidence: 99%